Outcome of Retinoblastoma Patients with High-risk Histopathological Features in a Tertiary Hospital - Patricia E. Cabrera, MD; Gary JV. Mercado, MD; Rolando Enrique D. Domingo, MD; Rafael Valenzuela, MD (Philippine Journal of Ophthalmology)
Objectives: To describe the outcome of patients with bilateral or unilateral retinoblastoma with high-risk histopathological features managed at a tertiary hospital in the Philippines.